2015
DOI: 10.1039/c4dt03631j
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt(iii)porphyrin to target G-quadruplex DNA

Abstract: G-quadruplex DNA ligands attract much attention because of their potential use in biology. Indeed they may interfere with G-quadrulex nucleic acid function in cells. Most of the G-quadruplex ligands so far reported (including also metal complexes) are large planar aromatic compounds that interact by π-π stacking with an external G-quartet of quadruplex. Porphyrins are well-known G-quadruplex ligands. We report herein a new porphyrin scaffold (meso-tetrakis(4-(N-methyl-pyridinium-2-yl)phenyl)porphyrin) able to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 58 publications
1
33
0
Order By: Relevance
“…The interaction with the G‐quadruplex grooves and loops is also taken into account for improving the selectivity for G‐quadruplex versus duplex DNA. Among the compounds able to target G‐quadruplexes, a number of metal complexes bearing aromatic ligands have been reported, including those of porphyrin, salphens, and salophens . In this context, we have designed a new extended planar ligand, based on a pyrazine core, namely dipyrazino[2,3‐ a :2′,3′‐ h ]phenazine (dph; Figure a).…”
Section: Introductionmentioning
confidence: 99%
“…The interaction with the G‐quadruplex grooves and loops is also taken into account for improving the selectivity for G‐quadruplex versus duplex DNA. Among the compounds able to target G‐quadruplexes, a number of metal complexes bearing aromatic ligands have been reported, including those of porphyrin, salphens, and salophens . In this context, we have designed a new extended planar ligand, based on a pyrazine core, namely dipyrazino[2,3‐ a :2′,3′‐ h ]phenazine (dph; Figure a).…”
Section: Introductionmentioning
confidence: 99%
“…[13] The most representative inorganic compounds that interact with G 4 -DNA are metal complexes of porphyrin [14] and salophen [15] ligands,p rovided that they are functionalized by cationic arms. We recently showed that nickel(II)-salophen complexes functionalized at both para positions by alkylmethylimidazolium groups [15e] bind strongly and specifically to G-quadruplexes.…”
mentioning
confidence: 99%
“…Bulky porphyrin derivatives H 2 -TMPipEOPP, H 2 -TMPy2PP, H 2 -GP, H 2 -DIGPor and H 2 -TPyEtCAP can perfectly discriminate between quadruplex and double-stranded DNA [63,69,71,[116][117][118][119][120]. Their binding constants for quadruplex DNA is comparable to that of best G4 ligands [120].…”
Section: Interaction Of Porphyrins With G-quadruplex Dnamentioning
confidence: 64%
“…Logically, due to their strong affinity for DNA duplex, none of these metalated TMPyP4 porphyrins are selective for G4 with respect to double-stranded DNA. In the case of bulky cationic porphyrins the influence of the central metal on the binding capacity of the metalated derivatives is less documented [69,71,119,120]. It seems that the presence of axial ligands on the metal does not always lower the binding capacity to quadruplex DNA.…”
Section: Interaction Of Porphyrins With G-quadruplex Dnamentioning
confidence: 93%